Archival management of educational staff in improving administrative services in senior high schools - Adian Purwo Nugroho; Priadi Surya; Tarso Tarso (Universitas Pendidikan Indonesia, 2025)
Well-organized archival management is a crucial element in supporting the efficiency of school administrative services. This study employed a qualitative descriptive approach to describe and analyze the implementation of educational archival management by administrative staff at SMA N 1 Sleman. Data were collected through observation, interviews, and documentation from January to March 2025. The findings indicate that archival management at SMA N 1 Sleman has been carried out systematically through the stages of planning, organizing, actuating, monitoring, and evaluating. The entire process, from receipt to record destruction, is conducted in an orderly manner according to established procedures and plays a strategic role in enhancing the quality of administrative services. Adequate facilities, staff training, and the leadership of the head of administration support the success of this management. However, challenges such as the school’s flood-prone location, limited storage space, and uneven staff competence remain obstacles. Improvement efforts, including digitization, the organization of document classification systems, and staff competency development, continue to be undertaken to enhance administrative efficiency and support the learning process. Abstrak Manajemen kearsipan yang terorganisasi dengan baik merupakan salah satu unsur penting dalam mendukung efisiensi pelayanan administrasi sekolah. Penelitian ini menggunakan pendekatan deskriptif kualitatif untuk mendeskripsikan dan menganalisis pelaksanaan manajemen arsip pendidikan oleh staf administrasi di SMA N 1 Sleman. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi pada periode Januari–Maret 2025. Hasil penelitian menunjukkan bahwa pengelolaan kearsipan oleh tenaga kependidikan SMA N 1 Sleman telah dilaksanakan secara sistematis melalui tahapan perencanaan, pengorganisasian, pelaksanaan, pengawasan, dan evaluasi. Proses mulai dari penerimaan hingga pemusnahan arsip dijalankan secara tertib sesuai prosedur, dan berperan strategis dalam meningkatkan mutu layanan administrasi sekolah. Keberhasilan pengelolaan arsip didukung oleh fasilitas yang memadai, pelatihan tenaga kependidikan, serta peran kepala tata usaha. Namun, kendala seperti lokasi yang rawan banjir, keterbatasan ruang penyimpanan, dan kompetensi staf yang belum merata masih menjadi tantangan. Upaya perbaikan melalui digitalisasi, sistem klasifikasi arsip, dan pengembangan kompetensi staf terus dilakukan untuk mendukung efisiensi administrasi dan proses pembelajaran. Kata Kunci: layanan administrasi; manajemen arsip; sekolah menengah atas; staf kependidikan